Impacto que generan los macro influencers de la provincia de Loja, en el comportamiento del consumidor local-Estudio aplicado a los estudiantes de la carrera de Administración de Empresas de la Universidad Nacional de Loja. - Quintuña González, María de los Ángeles (2022)
The present research work has as general objective to know the impact generated by the macro influencers of the province of Loja, in the behavior of the local consumer - case study applied to the students of the Business Administration Career, with the purpose of analyze the incidence generated by influencers in the behavior and purchase decision of the students of the CAE of the UNL, through the use of digital tools identifying positive and negative factors that affect the moment of receiving information, considering an affectation in decision-making regarding a product or service, allowing companies to make use of new advertising strategies generating positive stimuli in the behavior, positioning and purchase decision of consumers; the research was exploratory-conclusive that was achieved through the non-experimental quantitative method through the application of surveys and interviews, addressing the fulfillment of four specific objectives; In the first one, an internal analysis was carried out, where the results of the market research were analyzed to know the impact generated by the audiovisual content exposed in social networks and the external analysis was made through the PESTE analysis, knowing the evolution of the digital trade, its tools, actors and those who exert influence, in the digital ecosystem that affects commercial dynamics, analyzing the results of the interview with the influencers and the survey applied to 504 students of the UNL business administration career, contrasting information with the results obtained in the survey to know the perspective regarding the influence exerted by influencers on the purchasing behavior of students, achieving an analysis about the socio-cultural digital environment of content consumers and determining advertising tools and tactics that companies currently use to capture the attention of customers, using advertising strategies with influencers on social networks; concluding with an analysis regarding the importance of the study in the business world, once the research is done, the conclusions and recommendations are presented, in order to achieve optimal development of the proposed objectives.